Recent Advances in Educational Robotics - Chatzichristofis, Savvas A.; Zinonos, Zinon (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Over the past decade, the field of robotics has become increasingly popular among educators and researchers alike as a powerful tool for enhancing learning experiences. From preschool to high school students, educational robotics has shown the potential to improve cognitive and social skills, while facilitating interdisciplinary learning activities in various subjects such as science, mathematics, technology, and computer science. This reprint explores the emerging field of educational robotics, focusing on its creation, implementation, improvement, and validation of pedagogical activities, tools, and technologies. Our goal is to provide an overview of the latest research, trends, and best practices in the field, particularly emphasizing how educational robotics can enhance students' learning experiences in an engaging and interactive environment. Moreover, drawing on a literature review, this book explores the growing field of educational robotics and its potential to revolutionize science and technology education at all levels. Through hands-on, fun activities and an attractive learning environment, educational robotics can spark students' interest and curiosity, making learning a more enjoyable and rewarding experience. We hope this reprint will serve as a valuable resource for educators, researchers, and students alike, inspiring them to explore the exciting world of educational robotics and its potential to transform how we teach and learn.